Have You Been HIT? - Cross, J; Weisters, M; Aslam, R; Keeling, D; Handa, A (2011)
This review is specifically designed to aid the vascular surgeon in the management of heparin-induced thrombocytopenia (HIT). Heparin-induced thrombocytopenia is a rare complication of heparin administration, which poses significant morbidity and mortality. Its onset is usually 5 to 10 days after the heparin administration and should be suspected if platelet counts drop by at least 50%. Confirmation is given by the presence of HIT antibodies on an enzyme-linked immunosorbent assay (ELISA) or in functional platelet activation assays. The major complication is thrombosis and surprisingly bleeding is rare. Heparin must be stopped immediately if there is a clinical suspicion of HIT and alternative anticoagulation must be started. Anticoagulation is required for at least 2 to 3 months to prevent recurrence of thrombosis. Oral anticoagulation with warfarin should not be initiated until the platelet count has been recovered and there should be an overlap of at least 5 days between starting warfarin and stopping the alternative anticoagulant.